The impact of relational versus technological resources on e-loyalty: A comparative study between local, national and foreign branded banks - Kingshott, Russel; Sharma, Piyush; Chung, H. (Elsevier, 2018)
The emergence of online and mobile technologies has necessitated the need to re-examine the viability of relationship marketing in nurturing business-to-business service relationships. By drawing upon the resource-based view (RBV), social exchange (SE) theory and socio-technical systems (STS) theory, this research explores the differences in the process by which local, national and foreign branded banks are able to integrate their online platforms into their relational efforts. Data from a sample of 336 small and medium-sized business customers in the New Zealand banking industry shows that both offline and online service quality affect satisfaction with their e-banking services, which in turn affect the trust and commitment towards the bank and loyalty towards e-banking. In addition, the effect of trust and commitment on loyalty towards e-banking is significantly stronger for the local and national branded banks compared to foreign branded banks. Our findings extend current research on B2B relationship marketing and offer useful managerial insights for professional B2B services providers.